Tadao Ando. Collezione Pinault, Bourse de commerce, Parigi - Privitera, Francesca (Firenze Architettura, 2021)
The historical life of the Bourse de Commerce building in Paris is the inescapable starting point for the design of Tadao Ando’s Collection Pinault. The geometrical rigour of the cylindrical body designed by Ando, which is concentric to the rotunda of the Bourse de Commerce, reverberates echoes from the Enlightenment while gently urging the architecture towards the absolute, transforming the real into the universal.